TikTok-social media marketing practices and digital branding - Sabrina, Ade Josephin; Fernando, Yudi; Mergeresa, Fineke; Ikhsan, Ridho Bramulya; Sari Wahyuni-Td, Ika; Fernando, Erick (Institute of Electrical and Electronics Engineers Inc., 2024)
With the advancement of technology and the massive use of social media, many companies are looking at social media sites as their new way of promotion, one of which is the TikTok application. TikTok is one of the social media that provides opportunities for companies to build brands and promote their products or services by creating content that can attract, connect, and share information with customers. Therefore, this study aims to develop a theoretical mediation of TikTok's social media marketing practices and digital branding. Researchers have collected data obtained from questionnaires distributed online in the form of Google Forms to 170 user TikTok. This study found that TikTok's social media marketing practices and accessibility significantly and positively impact content sharing and digital branding. This research is expected to add and develop insights, information, thoughts, and knowledge for entrepreneurs in marketing through social media.